Comparative Study of Three Brands of Antidiabetic Drug, Empagliflozin Available in Karachi, Pakistan - Khadija Aslam; Safila Naveed; Fatima Qamar; Halima Sadia; Muhammad Ulusyar Khan; Tajala Aman (Journal of University Medical & Dental College, 2023)
Empagliflozin is a newer oral antidiabetic drug that treats people who have type-II Diabetes Mellitus. Empagliflozin reduces the reabsorption of filtered glucose and increases urine glucose excretion. The objective of the study is to analyze the physiochemical equivalence of different brands of Empagliflozin available in Pakistan. Three different brands of Empagliflozin were evaluated for their physicochemical properties and cost-effectiveness. These brands were analyzed for different physicochemical tests for weight variation, hardness, friability, disintegration, and dissolution. All the brands had an average hardness of ≥2kg, which was suitable for an immediate-release tablet. All three brands had shown their friability variation within ±1% range specified by United State Pharmacopoeia (USP). The standard deviation was also calculated. All three brands showed good disintegration and dissolution profile which would aid in maximizing bioavailability and satisfying patient needs. The present findings suggest that almost all three brands of Empagliflozin that are available in Karachi meet the USP specification for quality control analysis.